PERNIKAHAN DI BAWAH TANGAN KARENA DI BAWAH UMUR DI DESA SEMPARONG PARIT RADEN KECAMATAN SUNGAI KUNYIT KABUPATEN MEMPAWAH - Bahri, Muhammad Zainal; Marluwi, Marluwi; Muzammil, Sadulloh (Al-Usroh, 2023)
The purpose of This research is to find out: 1). What are the factors behind underhand marriages because they are underage 2). The impact of underhand marriages due to underage that occurred in Plangkeran Hamlet, Semparong Parit Raden Village, Sungai Kunyit District, Mempawah Regency. This study uses a qualitative research method with the type of field research (field research) and a sociological juridical approach. Sources of data used primary data in the form of interviews from the District KUA, Apparatus and the Semparong Parit Raden community, Sungai Kunyit District, Mempawah Regency whose subjects had been determined, namely the Head of KUA, Secretary , perpetrators of underhand marriages because they were underage. While secondary data in the form of Law no. 16 of 2019 concerning Marriage and the Compilation of Islamic Law (KHI). Data collection techniques are interviews and documentation. While the data analysis technique, the research carried out data reduction, data presentation and conclusions. Then for the inspection technique and the validity of the data using member check. The research results show that: 1). The factors of underhanded marriages because they are underage in Semparong Parit Raden Village, Sungai Kunyit District include educational factors, parental factors, and cultural factors. 2). The impact of underhand marriage due to underage in Semparong Parit Raden Village, Sungai Kunyit Subdistrict, includes the impact on making birth certificates for children and the impact of difficulties in obtaining education.